Is Islam a religion of tolerance or intolerance? an analysis of the qur'an, sunnah and interpretations of selected muslim scholars - Ushama, Thameem (Islamic Cultural Centre, 2018)
This study clearly establishes that Islam is a religion of magnanimous tolerance. Qualitative content analysis is applied to Qur'anic verses (Islamic Scripture) and the Prophet's Sunnah as well as to works from Muslim exegetes of global renown for their piety, integrity, commitment and sacrifice for the cause of the religion. The study explores the value of tolerance as referenced in the Qur'an and provides a survey of Western writers who view Islam as a religion of tolerance that historically advanced peacefully and without the sword. Examples of tolerance are cited in addition to models proving Islam's profound moderation. Key to this discourse is the position of non-Muslims (dhimmiyyuri) under Islamic rule, who pay tax for security and protection. Historical examples are also reviewed to show that Islam is a religion of tolerance.